2022
DOI: 10.3390/ijerph19159401
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Cross-Transmission between Inanimate Surfaces and Patients in Intensive Care Units under Real-World Conditions: A Repeated Cross-Sectional Study

Abstract: Background/Objectives: Contaminated surfaces play an important role in the nosocomial infection of patients in intensive care units (ICUs). This study, conducted in two ICUs at Edouard Herriot Hospital (Lyon, France), aimed to describe rooms’ microbial ecology and explore the potential link between environmental contamination and patients’ colonization and/or infection. Methods: Environmental samples were realized once monthly from January 2020 to December 2021 on surfaces close to the patient (bedrails, bedsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…As in this study, in a university hospital in France, they observed the growth of Gram-positive bacteria on surfaces analyzed in the research, such as computer keyboards and mice. 13 As these are surfaces used with high frequency and collectively, they pose a risk of transmitting pathogens to patients. Thus, protocols for hand hygiene for healthcare professionals and family members within healthcare services are recommended.…”
Section: Resultsmentioning
confidence: 99%
“…As in this study, in a university hospital in France, they observed the growth of Gram-positive bacteria on surfaces analyzed in the research, such as computer keyboards and mice. 13 As these are surfaces used with high frequency and collectively, they pose a risk of transmitting pathogens to patients. Thus, protocols for hand hygiene for healthcare professionals and family members within healthcare services are recommended.…”
Section: Resultsmentioning
confidence: 99%
“…B. megaterium can be found ubiquitously across diverse environments, including but not limited to soil, seawater, rivers, seafood and salt lakes. However, it is not considered a cause for nosocomial outbreaks, while up to this date mainly individual case studies were reported regarding its pathogenicity to humans [54][55][56].…”
Section: Discussionmentioning
confidence: 99%